Conceptualising learning from experience: Developing a model for facilitation - David Boud (Adult Education Research Conference, 1994)
The key feature of adult learning is the experience which learners bring with them. Whatever else they may be, adult educators are essentially workers with the experience of others. This paper describes a model designed to aid thinking about learning from experience and how it can be facilitated.